Escape from X inactivation is directly modulated by Xist noncoding RNA - Hauth, Antonia Raphaela; Panten, Jasper; Kneuss, Emma; Picard, Christel; Servant, Nicolas; Rall, Isabell; Pérez-Rico, Yuvia A.; Clerquin, Lena; Servaas, Nila; Villacorta, Laura; Jung, Ferris; Luong, Christy; et al. (Nature cell biology, 2026)
In placental XX females, one X chromosome is silenced during a narrow developmental time window by X-chromosome inactivation, which is mediated by Xist noncoding RNA. Although most X-linked genes are silenced during X-chromosome inactivation, some genes can escape. Here, by increasing its endogenous level, we show that Xist RNA can silence escapees well beyond early embryogenesis both in vitro, in differentiated cells, as well as in vivo, in mouse pre- and post-implantation embryos. We further demonstrate that Xist RNA plays a role in eliminating topologically associating domain-like structures spanning clusters of escapees, and this is dependent on SPEN. The function of Xist in silencing escapees and eliminating topological domains is initially fully reversible, but sustained Xist upregulation leads to irreversible silencing and CpG island DNA methylation of escapees. Thus, gene activity and three-dimensional topology of the inactive X chromosome are directly controlled by Xist, well beyond an early developmental time window.
Online veröffentlicht: 15. Dezember 2025
Gesehen am 19.02.2026